2017
DOI: 10.1002/acr.23219
|View full text |Cite
|
Sign up to set email alerts
|

Serious Infection Rates Among Children With Systemic Lupus Erythematosus Enrolled in Medicaid

Abstract: Objective To investigate the nationwide prevalence and incidence of serious infections among children with systemic lupus erythematosus (SLE) enrolled in Medicaid, the U.S. health insurance program for low-income patients. Methods From Medicaid claims (2000–2006) we identified children 5 to <18 years old with SLE (≥3 ICD-9 codes of 710.0, each >30 days apart) and lupus nephritis (LN; ≥2 ICD-9 codes for kidney disease on/after SLE codes). From hospital discharge diagnoses, we identified infection subtypes (ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 21 publications
4
25
1
Order By: Relevance
“…African Americans were more than 3.5 times more likely to have pneumonia and twice as likely to have bacteremia and sepsis. Our study agrees with two studies using the Medicaid administrative database that identified an increased risk of serious infections in African Americans compared to Caucasians with SLE, with the most common being bacteremia, pneumonia, and cellulitis [26, 27]. Our study builds upon these studies by including both inpatient and outpatient infections and offering a longer follow up of 9 years compared to the mean follow up of the studies of 2.5 years.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…African Americans were more than 3.5 times more likely to have pneumonia and twice as likely to have bacteremia and sepsis. Our study agrees with two studies using the Medicaid administrative database that identified an increased risk of serious infections in African Americans compared to Caucasians with SLE, with the most common being bacteremia, pneumonia, and cellulitis [26, 27]. Our study builds upon these studies by including both inpatient and outpatient infections and offering a longer follow up of 9 years compared to the mean follow up of the studies of 2.5 years.…”
Section: Discussionsupporting
confidence: 88%
“…This increased risk of infection in SLE is likely due to immunosuppressant medications, the disease itself, or an interaction between these factors [4648]. Two recent studies using the US Medicaid database investigated infection rates among different SLE patients but did not compare patients with SLE to matched controls [26, 27]. Our study establishes an increased risk of infection in African Americans with SLE compared to matched controls.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Infections were a major cause of death among paediatric patients in high-income countries. Serious infections are common among paediatric patients 45. Interventions to increase vaccination in children could further improve survival 46…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Arthritis Care & Research , the authors of “Serious Infection Rates Among Children With Systemic Lupus Erythematosus Enrolled in Medicaid” provide much needed information about this important outcome using a valuable data source . Infection is a common source of morbidity and mortality in adults with systemic lupus erythematosus (SLE), as these authors and other authors have previously demonstrated .…”
mentioning
confidence: 99%